Synthesis, activity evaluation, and pro-apoptotic properties of novel 1,2,4-triazol-3-amine derivatives as potent anti-lung cancer agents - Xian-yu Sun; Chun-yan Zhong; Qing-qing Qiu; Zhen-wang Li; Mei-yu Liu; Xin Wang; Cheng-hao Jin (Taylor & Francis Group, 2019)
In this study, a series of 4,5-bis(substituted phenyl)-4H-1,2,4-triazol-3-amine compounds was designed, synthesised, and evaluated to determine their potential as anti-lung cancer agents. According to the results of screening of lung cancer cell lines A549, NCI-H460, and NCI-H23 in vitro, most of the synthesised compounds have potent cytotoxic activities with IC50 values ranging from 1.02 to 48.01 µM. Particularly, compound 4,5-bis(4-chlorophenyl)-4H-1,2,4-triazol-3-amine (BCTA) was the most potent anti-cancer agent, with IC50 values of 1.09, 2.01, and 3.28 µM against A549, NCI-H460, and NCI-H23 cells, respectively, meaning many-fold stronger anti-lung cancer activity than that of the chemotherapeutic agent 5-fluorouracil. We also explored the effects of BCTA on apoptosis in lung cancer cells by flow cytometry and western blotting. Our results indicated that BCTA induced apoptosis by upregulating proteins BAX, caspase 3, and PARP. Thus, the potential application of compound BCTA as a drug should be further examined.